What is mutual about Public Service Mutuals?: critical realist study of mutualism within healthcare organisations in England - Conroy, Paul (2018)
Former Cabinet Office Minister Francis Maude once made the ambitious claim that one million public sector workers would own and run the services they provide by 2015. It never happened, but there are still approximately 110 Public Service Mutuals (PSMs) in England. Yet whilst mutuality permeates the discourse of this policy, mutualism in PSMs, as both ethos and practice, is under-theorised and under-researched. This thesis addresses these gaps using a critical realist approach.